New method for stress determination based on digital image correlation data. Issue 1 (2018) - Brosius, Alexander; Küsters, Niklas; Lenzen, Matthias
Abstract: Accurate material characterisation of anisotropic yielding behaviour for modern sheet metal requires the testing under multiaxial stress conditions like in the shear test or plane strain test. While most approaches include time-consuming finite element simulations for evaluation of inhomogeneous stress distributions, this paper shows a new method to determine stress data based directly on digital image correlation data. This accurate and efficient semi-analytical method can be used in direct stress analysis or inverse material parameter identification schemes as well. The methodology will be described and exemplarily results of the plane strain test and the shear test will be discussed.